Changes in lower dental arch dimensions and tooth alignment in young adults without orthodontic treatment - Bruno Aldo Mauad; Robson Costa Silva; Mônica Lídia Santos de Castro Aragón; Luana Farias Pontes; Newton Guerreiro da Silva Júnior; David Normando (Dental Press Editora, 2015)
OBJECTIVE: The aim of this longitudinal study, comprising young adults without orthodontic treatment, was to assess spontaneous changes in lower dental arch alignment and dimensions. METHODS: Twenty pairs of dental casts of the lower arch, obtained at different time intervals, were compared. Dental casts obtained at T1 (mean age = 20.25) and T2 (mean age = 31.2) were compared by means of paired t-test (p < 0.05). RESULTS: There was significant reduction in arch dimensions: 0.43 mm for intercanine (p = 0.0089) and intermolar (p = 0.022) widths, and 1.28 mm for diagonal arch length (p < 0.001). There was a mild increase of approximately 1 mm in the irregularity index used to assess anterior alignment (p < 0.001). However, regression analysis showed that changes in the irregularity index revealed no statistically significant association with changes in the dental arch dimensions (p > 0.05). Furthermore, incisors irregularity at T2 could not be predicted due to the severity of this variable at T1 (p = 0.5051). CONCLUSION: Findings suggest that post-growth maturation of the lower dental arch leads to a reduction of dental arch dimensions as well as to a mild, yet significant, increase in dental crowding, even in individuals without orthodontic treatment. Furthermore, dental alignment in the third decade of life cannot be predicted based on the severity of dental crowding at the end of the second decade of life.